Pengaruh Jarak Lendutan Pada Pegas Daun (Leaf Spring) Akibat Pembebanan - Sutarjo, Sandika Ariawan; Qiram, Ikhwanul; Rubiono, Gatut (Prodi Teknik Mesin Universitas PGRI Banyuwangi, 2019)
The transportation system generally prioritizes comfort and safety in terms of driving. To support this, a good suspension system is needed. Leaf springs are one of the suspension systems found in vehicles that function as vibration absorbers, as well as supporting vehicle frames. So it is necessary to do research on leaf spring spacing. To find out the distance of leaf spring deflection. This study focuses on the distance of deflection and the frequency of deflection on leaf springs, presumably there are characteristics of leaf spring spacing. The purpose of the study was to determine the distance of leaf spring deflection. From the results of the research carried out the results obtained The greater the static load that is given gives the effect of changing the shape of the plate that triggers a long change in each plate sheet. The biggest value of length change that occurs on the plate no (1) variations in the load of 15 kg which is equal to 99 cm.